Harmonization of food trade standards and regulations in ASEAN: the case of Malaysia's food imports - Devadason, Evelyn Shyamala; Chandran, V.G.R.; Kalirajan, Kaliappa (Wiley, 2018)
Regulatory heterogeneity continues to be identified as a challenge for food trade in the Association of Southeast Asian Nations (ASEAN) as the progress of harmonization of food standards among member states remains slow. Using a new and comprehensive database on nontariff measures (NTMs), this article examines the coverage, frequency, and diversity of NTMs for the food sector in Malaysia, and then estimates their impact on food imports from ASEAN. The food sector in Malaysia is found to be highly regulated, dominated by technical measures, namely, labeling for sanitary and phytosanitary and technical barriers to trade reasons, product quality, and restricted substances. The empirical results subsequently verify that, overall, technical measures are import restrictive. This article therefore contends that harmonization of food standards and regulations at the regional level is important for enhancing trade. However, building common ground for food safety regulations should be NTM- and sector-specific, to realize progress in terms of regulatory convergence. This is particularly true for the food sector, since complete harmonization is not practical and not politically feasible.